Infant And Children Feeding Models Assistance Models Using Pocket Book Media On Increasing Knowledge And Weight Increase To Slender Toddlers In The Village Of Merapi - Suaebah; Kammisari Dewi; Ayu Rafiony; Sopiyandi (Jurnal teknologi Kesehatan Borneo, 2021)
Thin nutrition is an acute nutritional problem, as a result of events that occur in a short time such as lack of food intake. The high prevalence of thin underweight nutrition in infants is influenced by three main factors namely poor quality of quantity pangan food consumption as a result of low family food security, poor patterns of foster care and low access to health facilities. The impact of underweight nutrition in infants can reduce intelligence, productivity, creativity, and very influential on the quality of HR. This type of research is a Quasi-Experiment with the design used is pretest-posttest design with control group design. The number of samples for each group of 28 people was taken by purposive sampling technique. Data analysis used parametric statistical tests and non-parametric tests. The results of the analysis of differences in knowledge before and after nutrition education in the two treatment groups there was no significant difference (p = 0.271). For weight gain in children under five given intervention that is the average weight of the pre-test 9.91kg and the average weight of the post-test was 10.13kg with the results of statistical tests showed that there was a significant weight gain (p = 0, 00). The conclusion of this study is that there is no difference between the treatment and control groups for the knowledge of mothers under five and there are differences in the treatment and control groups for toddler weight gain. Parents of toddlers are expected to have more access to information about health through various mass media such as newspapers, magazines, radio and television. In addition, it is also important to get a lot of information by participating in empowering organizations